3D SPH Numerical Simulation of Dam Break Flow around Fixed Obstacles - Naufal Saleh, Rezaldy; Tarwidi, Dede; ., Jondri (International Journal of Engineering and Technology, 2019)
Various efforts have been made to prevent coastal erosion. One of the efforts to prevent coastal erosion is to build breakwaters. This paper presents numerical modeling of fluid flow interaction with various shapes of breakwater. Fluid flow impact on different shapes of breakwater, i.e. trapezoidal prism, cylinder, and sphere has been investigated. The three-dimensional numerical modeling is purposed to decisive which breakwaters shape that can reduce the fluid velocity rapidly, compared to other tested breakwaters shapes. In this study, fluid motion is generated by dam break scheme. The fluid motion is governed by momentum and continuity equation. The equations of fluid motion are resolved by smoothed particle hydrodynamics (SPH) method. DualSPHysics, an open-source code based on SPH method, is applied to simulate fluid motion and the interaction with the blocks of breakwater. According to numerical results, the trapezoidal prism shape of breakwater can scale down the fluid velocity faster than the cylinder and sphere shape of breakwater with maximum velocity is about 2.20 m/s. Further, the cylinder shape yields the highest fluid velocity around the breakwater. The trapezoidal prism shape can be used as an effective breakwaterÂ Â